Pembuatan Hand Sanitizer dari Ekstrak Daun Salam (Syzygium polyanthum) Sebagai Alternatif Pembersih Tangan Bebas Alkohol - Sari, Nirmala; Fajriani, Fajriani; Nila, Ida Ratna (Universitas Negeri Surabaya, 2021)
Hand sanitizer products on the market generally contain alcohol which can cause dry hands and dehydration of the skin, therefore alternative ingredients that are skin-friendly and do not irritate the skin are needed such as the use of natural ingredients. One of them is bay leaf (Syzygium polyanthum). Salam plant is a plant that has antibacterial properties. The main ingredients that have antibacterial properties are flavonoids, tannins, essential oils, steroids, so that bay leaves can be used as a hand sanitizer to reduce alcohol use. The manufacture of bay leaf hand sanitizer is done by extracting the bay leaves with 96% ethanol solvent. The extraction results are then dissolved with other supporting materials which are certainly safe for health. It is hoped that the bay leaf hand sanitizer will be a safer alternative to hand sanitizers than alcohol-based hand sanitizers